Comparison of Inorganic and Organic Matter Sedimentation in a Natural Laboratory: A One-Year Study at Lough Hyne Marine Reserve, Ireland - Broszeit, Stefanie; Davenport, John; Jessopp, Mark; Harman, Luke; McAllen, Rob (Journal of Marine Biology, 2012)
Measuring sedimentation rates may provide useful information on the habitat preferences of marine organisms. To understand the effect of flow rates and meteorological conditions on sedimentation in the absence of other confounding factors, sedimentation of organic (OM) and inorganic (IOM) matters was measured at 6 sites in Lough Hyne Marine Reserve (a semienclosed marine lake) over the course of 13 months. During winter, both OM and IOM were imported to the Lough, peaking in December at Whirlpool, the site nearest to the Lough entrance, likely as a result of extreme weather conditions causing resuspension of matter outside the Lough. Highest inorganic matter (IOM) sedimentation occurred in December (47.36 gm−2d−1 at Whirlpool Cliff) and was related to November wind speeds (R2=0.39, P<0.001). Decreasing current speed also caused a decline in IOM sedimentation. Highest OM sedimentation occurred in December at Whirlpool (5.59 gm−2d−1), but was not related to meteorological conditions. No single environmental factor strongly influenced organic matter (OM) sedimentation. One-way ANOVAs on OM and log-transformed IOM data showed that sedimentation differed significantly amongst the six sites within the Lough. Increased plankton production in the Lough during summer led to increased OM sedimentation in areas of low current speed away from the entrance of the Lough.